Heavy quark(onium) at LHC: the statistical hadronization case - Andronic, Anton; Braun-Munzinger, P.; Redlich, K.; Stachel, Johanna (Journal of physics. G, Nuclear and particle physics, 2010)
We discuss the production of charmonium in nuclear collisions within the framework of the statistical hadronization model. We demonstrate that the model reproduces very well the available data at RHIC. We provide predictions for the LHC energy where, dependent on the charm production cross section, a dramatically different behavior of charmonium production as a function of centrality might be expected. We also discuss the case in elementary collisions, where clearly the statistical model does not reproduce the measurements.
Gesehen am 23.11.2022